Plasma Lipidomics Profiling of Developmental Dysplasia of the Hip in Tibet Plateau - Xiaogang Li; Jiamei Ji; Ping Li; De Yang; Nyima Yedron; Yanming Lei; Tao Chen; Jianchu Li; Ye Guo; Xiao Yang; Li Shi; Dan Qu (Health Care Science)
ABSTRACT Background Developmental dysplasia of the hip (DDH) is a prevalent pediatric condition with a multifactorial etiology. Its incidence varies geographically, with notably higher rates observed on the Tibet plateau. This study was performed to evaluate the lipidomics signatures associated with DDH by analyzing plasma samples. Methods Fifty infants were recruited, including 25 diagnosed with DDH and 25 age‐matched healthy controls. In addition to plasma samples, comprehensive laboratory test results and medical records were collected for each participant. An untargeted lipidomics profiling approach was employed to identify distinguishing metabolic signatures. Results Lipidomics profiles differed significantly between patients with DDH and healthy controls. Several differential metabolites were identified, including triacylglycerol (TAG)(17:0/18:1/20:1), TAG(17:0/17:0/17:0), phosphatidylethanolamine (PE)(10:0/26:4), TAG(17:0/18:0/18:0), TAG(16:0/17:0/22:1), TAG(16:0/18:0/22:0), TAG(17:0/19:0/19:0), TAG(13:0/20:0/20:0), TAG(18:0/18:0/22:0), and TAG(16:0/20:0/20:0). The primary lipid species showing differences were TAGs and PE. Conclusions Distinct shifts in lipidomics profiles were observed in infants with DDH. To the best of our knowledge, this study is the first to explore lipidomics signatures in patients with DDH. The combined assessment of TAG(17:0/18:1/20:1) and TAG(17:0/17:0/17:0) may serve as a potential diagnostic tool for DDH.